Neuroprotective effects of Pinus eldarica in a mouse model of pentylenetetrazole-induced seizures - Somaieh Mansouri; Mahmoud Hosseini; Farimah Beheshti; Mohammad-Ali Sobhanifar; Hassan Rakhshandeh; Akbar Anaeigoudari (Mashhad University of Medical Sciences, 2021)
Objective: Oxidative stress has pernicious effects on the brain. Pinus eldarica has antioxidant properties. We explored neuroprotective effect of P. eldarica against pentylenetetrazole (PTZ)-induced seizures.Materials and Methods: Male mice (BALB/c) were grouped as control, PTZ, Soxhlet (Sox) 100, Sox 200, Macerated (Mac) 100 and Mac 200 groups. Sox and Mac extracts (100 and 200 mg/kg) were injected during 7 days. Delay in onset of minimal clonic seizure (MCS) and generalized tonic- clonic seizure (GTCS) was measured. Number of dark neurons (DN) and levels of oxidative stress indicators in the hippocampus were evaluated.Results: Onset of MCS and GTCS was later in groups treated with the extracts than the PTZ group (p<0.01 and p<0.001). Number of DN in the hippocampus in the PTZ group was higher than the control group (p<0.001) while in the extract groups, was lower than the PTZ group (p<0.05, p<0.01 and p<0.001). MDA level was higher whereas total thiol level and activity of SOD and CAT were lower (p<0.001) in the PTZ group than the control group. MDA level in the Sox 100 (p<0.01), Sox 200 (p<0.001) and Mac 200 (p<0.01) groups was less than the PTZ group. Total thiol level in the Sox 200 (p<0.001), SOD in the Sox 100 (p<0.05), Sox 200, and Mac 200 and CAT in the Sox 200 (p<0.001) groups were higher than the PTZ group.  Conclusion: P. eldarica prevented neuronal death and reduced seizures caused by PTZ via improving brain oxidative stress.